Neuropsychology of the creative process. An educational approach - López-Fernández, Verónica; Llamas-Salguero, Fátima (Revista Complutense de Educación, 2017)
We live in a context and in a changing society, which requires individuals to adapt to the new circumstances in which we find ourselves. Creativity is one of the most important elements to consider in facilitating adaptation.. Therefore, it is particularly important to study from all scientific perspectives. Therefore, the objective of this study is to provide a better understanding of creativity from a neuropsychological approach given the multidimensional construct. It has conducted a review of research studying neuroscience creativity and vision of neuropsychological functions involved in this process, depending on the phase in which we face the creative activities that were established by Wallas (1926) proposal: preparation, incubation, illumination and verification. The results show that there there are cognitive functions especially relevant in each of the phases c and brain structures with high activation in the various stages of the creative process. Finally, it is proposed with this new perspective of the study of creativity, a starting point for future research.
Keywords: Creativity; cognitive functions; neuropsychology; creative process; education